Cell-Membrane Biomimetic Indocyanine Green Liposomes for Phototheranostics of Echinococcosis - Xinxin Xiong; Jun Li; Duyang Gao; Zonghai Sheng; Hairong Zheng; Wenya Liu (Biosensors, 2022)
Echinococcosis is an important zoonotic infectious disease that seriously affects human health. Conventional diagnosis of echinococcosis relies on the application of large-scale imaging equipment, which is difficult to promote in remote areas. Meanwhile, surgery and chemotherapy for echinococcosis can cause serious trauma and side effects. Thus, the development of simple and effective treatment strategies is of great significance for the diagnosis and treatment of echinococcosis. Herein, we designed a phototheranostic system utilizing neutrophil-membrane-camouflaged indocyanine green liposomes (Lipo-ICG) for active targeting the near-infrared fluorescence diagnosis and photothermal therapy of echinococcosis. The biomimetic Lipo-ICG exhibits a remarkable photo-to-heat converting performance and desirable active-targeting features by the inflammatory chemotaxis of the neutrophil membrane. In-vitro and in-vivo studies reveal that biomimetic Lipo-ICG with high biocompatibility can achieve in-vivo near-infrared fluorescence imaging and phototherapy of echinococcosis in mouse models. Our research is the first to apply bionanomaterials to the phototherapy of echinococcosis, which provides a new standard for the convenient and noninvasive detection and treatment of zoonotic diseases.